IMPLEMENTATION OF THE JOB TRAINING PROGRAM IN ENHANCING WORKFORCE QUALITY IN MEDAN CITY: A CASE STUDY AT THE CENTER FOR VOCATIONAL AND PRODUCTIVITY TRAINING MEDAN CITY - Ellen Tarigan; Erika Revida (Yayasan Wayan Marwan Pulungan, 2026)
This study examines the implementation of the job training program in improving the quality of the workforce in Medan City, conducted by the Center for Vocational and Productivity Training Medan under the Ministry of Manpower of the Republic of Indonesia. The purpose of this research is to analyze how the competency-based training program contributes to enhancing human resource capacity and reducing unemployment through effective policy implementation. A qualitative descriptive method was applied, supported by in-depth interviews, direct observation, and document analysis. Data were analyzed using an interactive model based on data reduction, data display, and conclusion drawing to obtain an in-depth understanding of the phenomenon. The findings indicate that the implementation of the training program has been effective and aligned with national labor development policies. Success was primarily influenced by four interrelated factors: clear communication, adequate institutional resources, positive disposition of implementers, and a well-structured bureaucracy. The study also found that the adaptability of the training program to industrial and regional development priorities particularly in the tourism and construction sectors has enhanced its relevance and impact. However, the absence of a systematic alumni tracking mechanism limits the evaluation of long-term outcomes. Overall, the program demonstrates that competency-based training can serve as a strategic approach to improving workforce competitiveness and promoting inclusive and sustainable economic growth in Indonesia.